2007
DOI: 10.1128/aac.01443-06
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Clostridium difficile Survives in Room Air on Moist Surfaces and in Gastric Contents with Reduced Acidity: a Potential Mechanism To Explain the Association between Proton Pump Inhibitors and C. difficile -Associated Diarrhea?

Abstract: Proton pump inhibitors (PPIs) have been identified as a risk factor for Clostridium difficile-associated diarrhea (CDAD), though the mechanism is unclear because gastric acid does not kill C. difficile spores. We hypothesized that the vegetative form of C. difficile, which is killed by acid, could contribute to disease pathogenesis if it survives in room air and in gastric contents with elevated pH. We compared the numbers of C. difficile spores and vegetative cells in stools of patients prior to and during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
147
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(150 citation statements)
references
References 33 publications
0
147
0
3
Order By: Relevance
“…This observation supports the hypothesis that gastric acid suppression by both PPI and H2RA increases the survival of the ingested of vegetative forms of C. difficile or permit the germination of spores in the upper intestinal tract. 39 A meta-analysis of studies supports the association of H2RA drugs and CDI. 10 It has also been suggested that the higher levels of bile salts in the upper gastrointestinal tract of patients with gastro-oesophageal reflux disease may be involved in spore germination, implying that the diseases for which H2RA or PPI are prescribed may have roles in the pathogenesis of CDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation supports the hypothesis that gastric acid suppression by both PPI and H2RA increases the survival of the ingested of vegetative forms of C. difficile or permit the germination of spores in the upper intestinal tract. 39 A meta-analysis of studies supports the association of H2RA drugs and CDI. 10 It has also been suggested that the higher levels of bile salts in the upper gastrointestinal tract of patients with gastro-oesophageal reflux disease may be involved in spore germination, implying that the diseases for which H2RA or PPI are prescribed may have roles in the pathogenesis of CDI.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has also been suggested that the higher levels of bile salts in the upper gastrointestinal tract of patients with gastro-oesophageal reflux disease may be involved in spore germination, implying that the diseases for which H2RA or PPI are prescribed may have roles in the pathogenesis of CDI. 39 Few studies to date have examined the risk of CDI relative to exposure to other classes of drugs aside from antibiotics and other gastric acid suppressing drugs. We felt exposure to distinct classes and total number of prescription medications might be useful variables to consider in assessing CDI risk and help to give perspective to the association with PPI, if one was found.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] The vegetative form of C difficile is susceptible to gastric acid, although spores are believed to be resistant. 41 A potential mechanism to explain the association of acid suppression medications with the development of CDI is increased survival of the vegetative forms of C difficile in response to decreased acid levels. 41 There is a paucity of studies assessing the effect of concomitant acid suppression medication use on outcomes in patients with CDI.…”
Section: Discussionmentioning
confidence: 99%
“…41 A potential mechanism to explain the association of acid suppression medications with the development of CDI is increased survival of the vegetative forms of C difficile in response to decreased acid levels. 41 There is a paucity of studies assessing the effect of concomitant acid suppression medication use on outcomes in patients with CDI. One hospital-based retrospective study revealed that 69% of CDI patients were taking PPIs, and of them, 21% did not respond to CDI treatment and 41% had CDI recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious enteric complications, such as a twofold increased risk of Clostridium (CDI) difficile infection [27] and a higher frequency of community [28] and ventilator acquired pneumonia [29]. PPIs may contribute to deficiencies of B12, iron and magnesium, acute interstitial nephritis and rebound acid hypersecretion with drug cessation [30].…”
Section: Harms Occur In Cirrhotic Patients and General Populationsmentioning
confidence: 99%